Cases of CHOP Chemotherapy - Unresponsive Primary Cutaneous Diffuse of Large B-Cell Lymphoma in Abdul Wahab Sjahranie Regional Public Hospital: A Case Presentation and Brief Review of Literature - Viky Hibatu Wafi; Zainal Abidin (http://dharmais.co.id/, 2023)
Introduction: Primary cutaneous diffuse large B-cell lymphoma (PCDLBCL) is a variety of B-cell neoplasms that are present in the skin with no evidence of extra-cutaneous disease at the time of diagnosis or even after 6 months of the diagnosis. Cutaneous B-cell Lymphoma (CBCL) comprises 25 to 35% of all primary cutaneous lymphomas. Due to the relative rarity of PCDLBCL, there are no completed randomized trials to clarify the optimal treatment. Reported therapy options include radiotherapy, multiagent chemotherapy, chemotherapy, polychemotherapy with rituximab, and rituximab as a single agent.Case Presentation: Several red nodular lesions on the back developed over 10 months are found in a 40-year-old woman. The first Incision biopsy revealed these lesions were malignant roundcell tumors. After being treated with 10 cycles of chemotherapy regimens comprising cyclophosphamide, doxorubicin, vincristine, dan prednisone (CHOP), there was a progressive response as several red nodular lesions are getting larger and turned into an ulcerated wound. Wide excisions and skin flaps were done. Anatomical pathology examination showed diffuse non-Hodgkin lymphoma, a large B cell that belongs to intermediate malignancy, as immunohistochemistry was positive for CD20 and CD45. The patient was then diagnosed with primary cutaneous diffuse large B-cell lymphoma and given rituximab, a CD20-targeted therapy. The patient was allowed to be discharged on the second day after surgery.Conclusions: This case report presents cases of CHOP chemotherapy-unresponsive PCDLBCL in Abdul Wahab Sjahranie Regional Public Hospital of Samarinda, East Kalimantan.